Kegiatan Mentoring Bulan I: Perkenalan dan Pembentukan TIM Program Pembinaan Mahasiswa Wirausaha (P2MW) 2025 (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service activity aims to describe the implementation of the first-month mentoring activity of the Student Entrepreneur Development Program (P2MW), which focuses on program orientation and team formation at Universitas Muhammadiyah Jambi. The activity was conducted in February 2025 and involved students participating in the P2MW program. A descriptive-participatory approach was applied through program socialization, facilitated team formation, interactive discussions, and group reflection. The results indicate that students gained a better understanding of the objectives and mechanisms of P2MW and were able to form entrepreneurial teams with clearer role distribution. In addition, the mentoring activity contributed to improving communication, teamwork, and students’ confidence in presenting business ideas. The first-month mentoring activity provides a positive initial foundation for the implementation of P2MW and supports the sustainability of student entrepreneurship development in subsequent stages.